AI: THE NEW LANGUAGE TEACHER - Makhmudova Xusniyabonu (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This paper talks about how AI can help people learn languages. It talks about how to use tools like Duolingo, ChatGPT, and Elsa Speak. The study’s goal is to find out how these tools help students learn. We used a way to review apps and get feedback from students. The results show that students learn more quickly and enjoy learning more. AI can also help you speak and fix your grammar. The paper talks about some new ways that AI is changing education and gives some examples.